Answer:
( 2x - 3 ) / 5
Step-by-step explanation:
2x - 6 = 5y - 3
2x - 6 + 3 = 5y
2x - 3 = 5y
y = ( 2x - 3 ) / 5
Answer:
Step-by-step explanation:
I believe your answer would be B, Bisect AB, but not be perpendicular to it.
1. the last one
2.the first one hope this helps.
Answer:
x = 13
Step-by-step explanation:
This question is based on Secant Secant theorem.
Secant Secant theorem gives us the following formula:
(AB + BD)AB = (AC + CE).AC
From the above question we have the following parameters
AB = 5
BD = x
AC = 7.5
CE = 4.5
Hence,
(AB + BD)AB = (AC + CE).AC
(5 + x)5 = (7.5 + 4.5)7.5
25 + 5x = 90
Collect like terms
5x = 90 - 25
5x = 65
x = 65/5
x = 13